Detection of hepatitis B surface antigen - Tan, Wen Siang; Tan, Geok Hun; Mohd Yusoff, Khatijah; Seow, Heng Fong (2004)
The invention relates to the identification of peptides that interact with hepatitis B surface antigen (HBsAg) and assays for detecting HBsAg in blood samples using the peptides associated with bacteriophages as diagnostic reagents.